Utopian fantasies of the perfected imperial prospect and fractured images of unresolved ambivalence and unsuppressed resistance : the Groote Schuur landscape considered as an imperial dream topography of Cecil John Rhodes, 1890-1929 - Gibson, Laura (African Studies, 2014)
The Groote Schuur landscape, probably more than anywhere else in South Africa, is a truly hybrid landscape. Many sets of big ideas were at play on this landscape between 1890 and 1929. At the end of the nineteenth century, Cecil Rhodes brought ideas of paternalism, imperialism and empire to the Estate and notions of creating a European space in Africa; Groote Schuur would be a meeting point where Africa and Europe would fuse in the same frame, where the wildness of Africa and the empire would energise the classicism of European civilisation. The idea of Britain in Africa perhaps found its most expressive form in the establishment of the European styled University of Cape Town on the slopes of a distinctly African mountain. As W J T Mitchell argues, landscape should be "seen more profitably as something like the dreamwork of Imperialism, unfolding its own movement in time and space from a central point of origin and folding back on Itself to disclose both utopian fantasies of the perfected imperial prospect and fractured images of unresolved ambivalence and unsuppressed resistance". Furthermore, this landscape is complicated by the dynamic shifts and changes that occurred in social and political thought during this period. Ideas on paternalism, of Britain having a pastoral role in Africa, were increasingly overshadowed by ideas of indirect rule and nationalism after Union in 1910 and then by the beginnings of ideas on absolute racial separation. A sense of trusteeship was increasingly supplanted by ideas of partnership between coloniser and colonised. These contestations are all played out on the landscape, just as they were in other fields and are complicated further by the enduring legacy of Rhodes. Intention: In this mini dissertation I will examine in detail four elements of the Groote Schuur Estate to see how these "big ideas" of dream topographies are played out on this specific landscape. 1890 is a natural starting point for my project since this was the year in which Rhodes took up permanent residency at Groote Schuur, acquired property that extended from "Mowbray southwards to Constantia" and began shaping the landscape according to his will. However, I have extended my study beyond the year of Rhodes' death in 1902, to 1929. This later date was the year that the University of Cape Town moved into its new Groote Schuur campus, and celebrated its centenary anniversary here. The event was seen as marking the conclusion of one of Rhodes' earlier dreams; the founding of a "teaching University in the Cape Colony... under the shadow of Table Mountain".